Mutations and Phylogenetic Analyses of SARS-CoV-2 Among Imported COVID-19 From Abroad in Nanjing, China - Zhao, Ning; Zhou, Nan; Fan, Huafeng; Ding, Jie; Xu, Xingyu; Dong, Xiaoqing; Dong, Xiaoxiao; Xu, Dandan; Min, Xiaoyu; Yu, Yan; Gong, Hongjin; Mao, Lingfeng; et al. (Frontiers in Microbiology, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a pandemic and is threatening human health globally. The rapid genome sequencing and bioinformatic analysis of SARS-CoV-2 have become a helpful tool in the battle against the COVID-19. Here, we report the genetic characteristics, variations and phylogenetic analysis of SARS-CoV-2 sequenced from 42 clinical specimens. The complete genomes sequencing of SARS-CoV-2 were performed using Oxford Nanopore sequencing. All genomes accumulated mutations compared to the Wuhan-Hu-1 (GenBank Accession No: MN908947.3). Our data of the 42 whole genomes revealed 16 different lineages. The B.1.1 lineage was the most frequent, and 5, 2, 2, 3, and 1 sequences were classified as lineages of B.1.1.7, B.1.351, P.1, B.1.617.2, and C.37, respectively. A total of 328 nucleotide mutation sites were found in 42 genomes, among which A23403G mutation (D614G amino acid change in the spike protein) was the most common substitution. The phylogenetic trees of 42 SARS-CoV-2 sequences and GISAID-available SARS-CoV-2 sequences were constructed and its taxonomic status was supported. These results will provide scientific basis for tracing the source and prevention and control of SARS-CoV-2 imported from abroad in Nanjing, China.